Satu Kajian Ke Atas Penglibatan Remaja Dalam Masalah Penyalahgunaan Dadah Dan Ketum (Mitragyna Speciosa) Di Malaysia - Suhaimi, Mohd Aizuddin Azuan (2024)
National Anti-Drug Agency (AADK) found most of the newly detected adolescent drug users were engaged in unsafe sexual behaviours and abusing ketum (Mitragyna speciosa) in the country. While they remain unapproachable and given the paucity of studies involving them, this mixed-method, cross-sectional study aims to investigate the risky sexual behaviours and motives of ketum use. A total of 80 adolescents (age between 13 and 19 years) who were undergoing mandatory drug rehabilitation under Section 6 of the Drug Dependants (Treatment and Rehabilitation) Act of 1983 were recruited through purposive sampling from two formal rehabilitation centres (PUSPEN). All the study data was collected with a self-administered, semi-structured questionnaire, while 21 respondents also participated in the in-depth, face-to-face interviews. Majority were males (70%, n=56/80), only 24 respondents were females. Most Malays (96%, n=77/80), while the samples mean age was 18.2 years (SD=1.40). Sixty-three percent (n=50/80) used methamphetamine only, and the samples mean duration of drug use was 3.15 years (SD=1.5). Sixty-nine percent had engaged in sex previously. High-risk sexual behaviours include having unprotected sex (11%), sex with more than one person (84%), and sex under the influence of drugs (94%). About 44% of the sample had intimate partners who use drugs. Most respondents (64%) were aware of the advantages of safe sex and were familiar with HIV transmission modes (74%). Results from multivariate logistic analysis indicate that females had significantly higher odds of engaging in unprotected sex and having intimate partners who use drugs, whereas, males were, however, more likely to have sex under the influence of drugs.